2018
DOI: 10.1038/s41585-018-0066-1
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic lymph node dissection during radical cystectomy for muscle-invasive bladder cancer

Abstract: Radical cystectomy is the gold-standard treatment option for muscle-invasive and metastatic bladder cancer. At the time of cystectomy, up to 25% of patients harbour metastatic lymph node deposits. These deposits most frequently occur in the obturator fossa, but can be as proximal as the interaortocaval region. Thus, the use of concurrent pelvic lymph node dissection (PLND) with cystectomy has been increasingly reported. Data from studies including many patients suggest substantial oncological benefit in PLND c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 58 publications
0
66
0
Order By: Relevance
“…Abol-Enein et al (30) demonstrated that the 5 year disease-free survival rate of patients undergoing extended LND in a non-randomized prospective cohort study was 66.6% (extended lymphadenectomy) vs. 54.7% (standard lymphadenectomy). In addition, extended LND can also reduce the probability of pelvic organ metastasis (27,31). Although numerous studies reported this result, some controversies exist.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Abol-Enein et al (30) demonstrated that the 5 year disease-free survival rate of patients undergoing extended LND in a non-randomized prospective cohort study was 66.6% (extended lymphadenectomy) vs. 54.7% (standard lymphadenectomy). In addition, extended LND can also reduce the probability of pelvic organ metastasis (27,31). Although numerous studies reported this result, some controversies exist.…”
Section: Discussionmentioning
confidence: 92%
“…extended LND and super-extended LND (15). Previous studies reported that expanding the extent and number of LNDs has a crucial impact on the prognostic significance, not only for lymph node-positive patients but also for the postoperative prognosis of lymph node-negative patients (26,27). In addition, it was reported that LND might be an independent prognostic factor for the prognosis of patients with BCa, since extended LND can reduce micrometastasis (28).…”
Section: Discussionmentioning
confidence: 99%
“…Positive surgical margins have a reported incidence of 1-10% in conventional UC across stages [15], and up to 12% in cases of extravesical disease extension [16]. Nodal-positive disease at RC can be found in approximately 25% in general, and up to 34% in patients with advanced pT stage [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…11 (17) 82 (20 Each histology subgroup received a median of four NAC cycles. In the PUC subgroup, using chi squared test, no significant association was identified between NAC and pT0N0 (p = 0.96), extravesical disease at surgery, (p = 0.84), pN+ status (p = 0.72), margin positivity (p = 0.93), LVI+ (p = 0.33) or CIS+ (p = 0.14).…”
Section: Neoadjuvant Chemotherapymentioning
confidence: 99%
“…Publications strongly suggest that all patients undergoing radical cystectomy for bladder cancer should undergo concomitant extended pelvic lymph node dissection (ePLND) because of the positive effect on correct staging and survival [5]. Although controversy surrounds PLND levels, many researchers agree that ePLND shows superior survival rates and correct staging compared to limited PLND [6,7] and superextended PLND provides no additional survival benefits due to the potential for increased operation time and patient morbidity [8]. In addition, it is reported that meticulous dissection is more important than the number of nodes removed [7,8].…”
Section: Introductionmentioning
confidence: 99%